SISTEM PENDUKUNG KEPUTUSAN UNTUK REWARD PENJUALAN PADA CHIYO NATHA TASIKMALAYA MENGGUNAKAN METODE MAUT - Warnilah, Ai Ilah; Pertiwi, Melisa Winda; Bela, Yuliana - (Universitas Bina Sarana Informatika, 2024)
Such as macroni, basreng, and lidi noodles located in the city of Tasikmalaya, West Java. In 2012, the owner started selling the snacks to make ends meet.With the rapid development of Chiyo Natha at this time it has spread widely outside the area so that many partners want to do business with Chiyo Natha. As for the problems that exist at Chiyo Natha, namely giving sales rewards every three months to distributors who are not on target and still manual, therefore the author will provide proposals to be able to overcome these problems by using the MAUT Method Decision Support System.It is hoped that with this system the results obtained will be better for Chiyo Natha in the future and can maximize employee performance in calculating sales rewards and the information obtained is more effective and efficient. From the results of the author's analysis, the highest reward was obtained with a value of 0.6525. With the existence of a Decision Support System for Giving Rewards, it is hoped that employee performance can be maximized in calculating sales rewards at Chiyo Natha Tasikmalaya.